Digital Transformation and High-Quality Development of Enterprises: Evidence from China - Hong , Wanying (Transactions on Economics, Business and Management Research, 2024)
The swift progression of digital technology is leading to substantial shifts and evolutions within enterprises. In the evolving environment characterized by the integration of digital technologies and the physical market, it’s essential to examine the effects of digitalization on the path of enterprises towards attaining superior growth quality. This study utilizes panel data from A-share listed companies in China’s equipment manufacturing sector, spanning from 2013 to 2021, to perform an empirical analysis on the influence and mechanisms of digital transformation in fostering the progress of these companies towards high-quality growth. The results reveal that digital transformation plays a significant role in promoting high-quality development among equipment manufacturing enterprises, and these results remain consistent after implementing various tests to mitigate endogeneity and confirm the findings’ reliability. The examination of mechanisms suggests that digital transformation significantly contributes to the advancement of equipment manufacturing companies by alleviating financial constraints, improving internal control quality, and facilitating the integration of environmentally friendly innovation technologies. Moreover, the impact of digital transformation on elevating the quality of development within equipment manufacturing companies is notably more pronounced in privately-owned firms, those located in the eastern region, and businesses classified as high-tech. This highlights how the nature of ownership, geographical location, and technological classification further amplify the benefits of digital transformation for high-quality growth in the sector. These findings offer a theoretical basis for assessing the economic implications of enterprises’ digital transformation and for shaping relevant governmental policies.